Studies of Electrical and Thermal Characteristics of Natural Ester Immersed Transformer Compared with Mineral Oil Immersed and Palm Oil Immersed Transformer - Maneerot, S.; Jariyanurat, K.; Nimsanong, P.; Bunlaksananusor, C.; Kunakorn, A.; Pattanadech, N. (My University, 2018)
This paper represents studies of electrical and thermal characteristics of natural ester immersed transformer compared with mineral oil immersed and palm oil immersed transformer by designing and constructing three single-phase transformers with rated 400/1000V 10kVA, the first transformer used mineral oil, the second transformer used natural ester, and the last one used palm oil, for studying about electrical properties, thermal properties and chemical properties under different types of liquid insulation in each transformer. First of all, three types of liquid insulation were tested with many item such as dielectric breakdown strength according to IEC 60156, dielectric dissipation factor following to ASTM D924-99. Besides, dielectric breakdown strength of impregnated pressboard were also investigated following to IEC 60243-1. Moreover, the chemical properties of the insulations were tested for some properties such as moisture content in accordance with ASTM D1533-00, interfacial tension according to ASTM D0971-99, acidity according to ASTM D974-02. After that, transformers were operated at 100 % of designed rated with inductor load for four months by which the temperature, current, and voltage were recorded every hour. Every two months, the liquid insulation was sampling from each transformer to be investigated. From the test results, they can concluded that natural ester are the alternative liquid insulation for using instead of mineral oil. In part of palm oil, it has good properties but it has the weak points about dielectric dissipation factor and acidity which are higher than the others.
Keywords: electrical characteristics; immersed transformer; mineral oil; natural ester; palm oil; thermal characteristics